2019
DOI: 10.3390/su11247172
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Effectiveness of Greenhouse Gas Reduction Policy for Office Building Design in South Korea

Abstract: This paper examines the effectiveness of South Korea’s policy for reducing greenhouse gas (GHG) emissions in office buildings and evaluates if national targets can be met. A sample of office buildings was categorized into two groups—conventional (Group A) and new (Group B)—based on when their construction was approved. Furthermore, data regarding the three design elements of the building envelope, that is building form, window systems, and U-values were collected. By statistically processing data of each eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In this final scenario, the monthly electrical energy saving for airconditioning is approximately 5.1 kWhe/m 2 per unit envelope area, with an associated reduction in greenhouse gas emissions up to 6.36 kg CO 2 eq/m 2 per unit envelope area, assuming continuous operation of the HVAC systems. Kwak et al (2019) also found that improvement options of envelope features of four buildings yielded a 72% and a 24% drop in annual cooling energy consumption, resulting in an average decrement of 62% in CO 2 emissions. The study then concluded that window space, window eaves, window characteristics, exterior wall insulation thickness, draft prevention, shading, landscaping features and control of solar energy, considerably reduce heating-cooling energy consumption, the amount and cost of natural gas, electricity, annual greenhouse gas emissions from heating and cooling energy.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In this final scenario, the monthly electrical energy saving for airconditioning is approximately 5.1 kWhe/m 2 per unit envelope area, with an associated reduction in greenhouse gas emissions up to 6.36 kg CO 2 eq/m 2 per unit envelope area, assuming continuous operation of the HVAC systems. Kwak et al (2019) also found that improvement options of envelope features of four buildings yielded a 72% and a 24% drop in annual cooling energy consumption, resulting in an average decrement of 62% in CO 2 emissions. The study then concluded that window space, window eaves, window characteristics, exterior wall insulation thickness, draft prevention, shading, landscaping features and control of solar energy, considerably reduce heating-cooling energy consumption, the amount and cost of natural gas, electricity, annual greenhouse gas emissions from heating and cooling energy.…”
Section: Introductionmentioning
confidence: 89%
“…Kwak et al (2019) also found that improvement options of envelope features of four buildings yielded a 72% and a 24% drop in annual cooling energy consumption, resulting in an average decrement of 62% in CO 2 emissions. The study then concluded that window space, window eaves, window characteristics, exterior wall insulation thickness, draft prevention, shading, landscaping features and control of solar energy, considerably reduce heating-cooling energy consumption, the amount and cost of natural gas, electricity, annual greenhouse gas emissions from heating and cooling energy.…”
Section: Introductionmentioning
confidence: 89%
“…The greenhouse effect has become a widespread issue faced by the whole world and has a significant impact on human survival and progress 1 . “Carbon emissions” is an abbreviation for greenhouse gas emissions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, flexible research and flexible modeling approaches were developed with a focus on nonresidential buildings, such as offices, sales, accommodation, educational, and cultural structures [17]. Moreover, the impact and effectiveness of building energy policies on GHGs were investigated with the developed reference building models targeting office buildings in South Korea [18]. A new type of reference building model was developed with the proposed methodology targeting religious buildings in the US [19].…”
Section: Introductionmentioning
confidence: 99%